Development of Ibis Paint X-Based Learning Video Media on Metamorphosis Content to Improve Students’ Understanding of Third Grade Elementary School - Intan Dihni Arsika; Novanita Whindi Arini (Universitas Labuhanbatu, 2025)
Background: Science learning in elementary schools often faces challenges, particularly in students' difficulty understanding the material. These difficulties stem from a lack of interest in learning due to the unappealing learning media used in class. This problem certainly requires a relevant solution. The use of engaging learning media, such as instructional videos, can be utilised in learning. These instructional videos can be developed using various platforms, one of which is Ibis Paint X. The purpose of this study is to develop educational videos as learning media for science instruction in third-grade. Methodology: The research method employed is Research and Development (R&D), utilising the ADDIE Model, which comprises five stages: analysis, design, development, implementation, and evaluation. Findings: Based on the results of the validity test, the assessment of media experts obtained (79%) with the criteria of